Giant thalamic hydatid cyst: a rare clinical presentation - Krishnegowda, Chetana (International Journal of Research in Medical Sciences, 2016)
Hydatid disease is a parasitic infestation caused by tapeworm Echinococcus. Cystic hydatidosis commonly involves liver and lungs and rarely the brain. A young female patient presented with progressive weakness of left upper and lower limb of one and half year duration at the time of admission. On evaluation, computed tomography (CT) scan of the brain showed a giant thalamic cystic lesion in the right cerebral hemisphere. Patient underwent right frontal craniotomy and excision of the cyst immediately. Histopathology was suggestive of hydatid cyst. Patient’s neurological condition improved and was subsequently treated with oral anti-helminthics. Surgical excision is the standard care of treatment.